PENGARUH CYBERCULTURE PADA TRADISI KEAGAMAAN: STUDI LITERATUR TENTANG ADAPTASI DAN TRANSFORMASI BUDAYA - Amin, Husna; Aslan, Aslan; Ram, St. Wijdanah (Penerbit Lafadz Jaya, 2025)
This study explores how cyberculture, or digital culture formed through the use of the internet and modern technology, influences religious traditions. In this digital age, religious traditions are not only striving to survive but also evolving through adaptation and transformation. Cyberculture offers new ways for individuals to interact with their beliefs, such as through online worship and theological discussions on social media. This enables the dissemination of religious information in a more widespread and inclusive manner. However, these changes also present challenges, including those related to traditional authority and the authenticity of spiritual experiences. This study highlights the importance of balancing technological progress with preserving the essence and fundamental values of religious traditions. Thus, this research aims to provide insights into how religion can remain relevant and meaningful while supporting communities in the digital age.